2007
DOI: 10.1111/j.1365-2036.2007.03358.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to gastroprotection and the risk of NSAID‐related upper gastrointestinal ulcers and haemorrhage

Abstract: SUMMARY BackgroundUpper gastrointestinal (UGI) complications are a well-recognized risk of NSAID treatment, requiring preventive measures in high-risk patients. Adherence to gastroprotective agents (GPAs) in NSAID users has been suggested to be suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 30 publications
(59 reference statements)
4
48
0
1
Order By: Relevance
“…4 However, despite clinical guidelines, evidence from practice suggests that gastroprotective co-therapy strategies are underutilized by physicians 7 and poorly adhered to by patients. [8][9][10][11] Partly as a result of this, there has been growing interest in the use of fixed-dose combination therapies of NSAIDs with gastroprotective agents in a single tablet to, among other potential benefits, improve patient adherence. PN 400 (VIMOVO; AstraZeneca, Wilmington, DE, USA and POZEN, Inc., Chapel Hill, NC, USA) is a fixed-dose combination of EC naproxen 500 mg and immediate-release (IR) esomeprazole 20 mg that is in development for the treatment of the signs and symptoms of osteoarthritis, rheumatoid arthritis and ankylosing spondylitis in patients at risk for developing NSAIDassociated gastric ulcers.…”
Section: Publication Datamentioning
confidence: 99%
“…4 However, despite clinical guidelines, evidence from practice suggests that gastroprotective co-therapy strategies are underutilized by physicians 7 and poorly adhered to by patients. [8][9][10][11] Partly as a result of this, there has been growing interest in the use of fixed-dose combination therapies of NSAIDs with gastroprotective agents in a single tablet to, among other potential benefits, improve patient adherence. PN 400 (VIMOVO; AstraZeneca, Wilmington, DE, USA and POZEN, Inc., Chapel Hill, NC, USA) is a fixed-dose combination of EC naproxen 500 mg and immediate-release (IR) esomeprazole 20 mg that is in development for the treatment of the signs and symptoms of osteoarthritis, rheumatoid arthritis and ankylosing spondylitis in patients at risk for developing NSAIDassociated gastric ulcers.…”
Section: Publication Datamentioning
confidence: 99%
“…In particular increasing adherence to GPAs is important in reducing the risk nsNSAID-related UGI events. [16][17][18] As another preventive strategy, COX-2-selective inhibitors were developed to improve the gastrointestinal safety of NSAID therapy, especially in high-risk patients such as elderly (aged ≥65 years) patients, those with a history of UGI events or concomitantly using anticoagulants, antiplatelets or corticosteroids. After the introduction of coxibs, it was shown that they indeed were associated with less gastrointestinal toxicity as compared to the traditional non-selective NSAIDs alone.…”
Section: Discussionmentioning
confidence: 99%
“…28 Though the implementation of preventive strategies has increased in recent years, there is still room for considerable improvement with regard to use of preventive strategies during NSAID therapy. 16,29 In order to investigate which preventive strategy is superior with regard to UGI safety, head-to-head comparisons between coxibs and NSAIDs combined with GPAs have been performed in randomized studies. These studies showed no preference of one strategy over the other.…”
Section: Discussionmentioning
confidence: 99%
“…терапии №2 фа-культета повышения квалификации и переподготовки кадров; 210023 Витебск, просп. Фрунзе, 27; e-mail: ruselikelena@mail.ru дуцированной приемом нестероидных противовоспали-тельных средств (НПВС-гастропатии), влияет соблюде-ние схемы («приверженность») терапии гастропротектив-ными средствами [3,4]. Лечение и профилактика ЭЯП СО пищевода, желудка и двенадцатиперстной кишки (ДПК) при приеме НПВС, в частности у больных ревматоидным артритом (РА), обусловливает необходимость длительно-го применения ингибиторов протонного насоса (ИПН).…”
Section: соблюдение схемы терапииunclassified